Age did not affect the rate of subsequent hysterectomy following hysteroscopic surgery: A population‐based retrospective cohort study from 2000 to 2020 - Huang, Wan‐Ting; Wang, Jeng‐Hung; Ding, Dah‐Ching (International journal of gynecology and obstetrics, 2025)
Objective Previous studies found younger age was associated with an increased risk of hysterectomy after hysteroscopic surgeries (HS) due to abnormal uterine bleeding (AUB). The present study aimed to evaluate the effect of age on the incidence of hysterectomy after HS for treating AUB in Taiwan. Methods This was a nationwide population‐based retrospective cohort study which utilized the Taiwan National Health Insurance Database. The present study involved 4150 participants who underwent HS due to AUB. The study focused on females aged ≥40 years diagnosed with AUB who underwent HS between 2000 and 2020. Hysterectomy outcomes were analyzed using the Cox proportional hazards model, and age was categorized into three groups (40–44, 45–49, and 50–55 years). Statistical significance was set at P < 0.05. Results This study involved 4150 participants with an average age of 46.1 years, categorized into the following age groups: 40–44 years (39.6%), 45–49 years (38.8%), and 50–55 years (21.6%). Approximately 8.1% of participants required hysterectomy treatment; the highest incidence was observed in the 40–44‐year age group (8.6%). The median time from HS to hysterectomy varied across age groups, ranging from 0.25–2.78 years. The presence of uterine myoma (adjusted hazard ration [aHR]: 2.11; 95% CI: 1.70–2.64; P < 0.0001) and adenomyosis (aHR: 10.24; 95% CI: 8.17–12.85; P < 0.0001) significantly increased the risk of hysterectomy. Kaplan–Meier survival curves demonstrated a comparable likelihood of hysterectomy across age groups within 5 years post‐HS, with most occurrences occurring in the initial 5 years. Conclusion Our study found no age effect on subsequent hysterectomy after HS. This study contributes to a significant understanding of HS outcomes, aiding information for patients seeking AUB surgical options. Synopsis The median time from hysteroscopic surgeries to hysterectomy varied across age groups, ranging from 0.25 to 2.78 years, without significant differences among the three groups.